Analisis Perkembangan Emosi Anak Usia Dini - Sukatin, Sukatin; Chofifah, Nurul; Turiyana, Turiyana; Paradise, Mutia Rahma; Azkia, Mawada; Ummah, Saidah Nurul (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2020)
Emotional development is increasingly understood as a crisis in the development of children. From the early development period, babies show a sense of security in their families if their needs are met by their environment. Babies will explore through touch and rasal. The learning process at this time will influence the development at a later stage. Early age is also called the golden development stage (golden ege). At this stage most brain cells function as controllers of each activity. By paying attention and understanding the emotions of children, can help teachers accelerate the learning process that is meaningful and permanent. The ability of early childhood to manage emotions is part of the maturation of emotional development of children in the transition from preoperative to concrete operational period. The ability of early childhood to manage their own emotions can be seen from the dimension of children's ability to use their emotions positive.